Queer singapore : illiberal citizenship and mediated cultures - Yue, Audrey; Zubillaga-Pow, Jun (Queer Asia., 2012)
Singapore remains one of the few countries in Asia that has yet to decriminalise homosexuality. Yet it has also been hailed by many as one of the emerging gay capitals of Asia. This book accounts for the rise of mediated queer cultures in Singapore's current milieu of illiberal citizenship.